Modulation of cell recruitment by anti-inflammatory agents in antigen-induced arthritis. Issue 11 (1st November 2002) - López-Armada, M J; Sánchez-Pernaute, O; Largo, R; Diez-Ortego, I; Palacios, I; Egido, J; Herrero-Beaumont, G
Abstract : Objective: To study the effect of meloxicam (MXC) and diclofenac (DCF) on the recruitment of leucocytes during acute experimental arthritis. Methods: Rabbits with antigen-induced arthritis were treated with MXC, DCF, or not treated. After 48 hours, synovial fluid (SF) leucocyte influx and prostaglandin E2 (PGE2 ) levels were evaluated. Interleukin 8 (IL8) and monocyte chemotactic peptide-1 (MCP-1) expression and synthesis were studied in the inflamed tissues. Results: Arthritic knees showed synovial effusion with a high leucocyte count and PGE2 concentration, and an increased expression of IL8 and MCP-1. Both non-steroidal anti-inflammatory drugs (NSAIDs) reduced PGE2 levels and the polymorphonuclear cell (PMN) concentration in SF, while the mononuclear cell (MN) concentration was unchanged in the treated groups in comparison with controls. A definite reduction of IL8 levels was obtained with the treatments, but the drugs did not prevent the up regulation of MCP-1. Conclusion: The effect of these NSAIDs in acute arthritis may be related to the down regulation of IL8 production. The results suggest a differential effect of anti-inflammatory drugs on PMN and MN recruitment to the joint.